Implementations of Industry 4.0 in the German automotive industry - Knigge, Felix Alexander; Vlčková, Jana; Kohut, Dominik; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2022)
The aim of the thesis is to analyze how the Industry 4.0 technologies are being implemented the German automotive sector. This goal is tackled by firstly outlining the specifics of the automotive industry, with an emphasis on its production. Secondly, insights are given into the automotive sector in Germany, including its importance for the German economy. Thirdly, the topic of Industry 4.0 is elaborated on. This does not only include the reshaping of production processes, but also major sub technologies that either contribute to shape the fourth industrial revolution and/or serve as Industry 4.0 enablers. Fourthly, based on multiple-case studies of selected key players of the German automotive industry, examples of the implementation of Industry 4.0 technologies are given. This also includes the respective companies' motivations to introduce the considered technologies, as well as their outcomes after implementation.
Vedoucí práce: Jana Vlčková
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2022
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2022
Způsob přístupu: Internet
Keywords: international business [obor bakal. práce]; bakalářské práce; bachelor's theses